Introduction to the thermodynamics of materials - Gaskell, David R. (Taylor and Francis, 1995)
This edition acts as an introductory text, simultaneously demonstrating the underlying principles and applicability of thermodynamics to the behavior of non-metallic materials and to the transformation of metallurgy materials.